2021
DOI: 10.1136/bmjopen-2021-050826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of healthcare strikes on patient mortality: a protocol for a systematic review and meta-analysis of observational studies

Abstract: IntroductionA strike is a collective, temporary and calculated action, which involves a temporary stoppage of work. For healthcare professionals strike action poses a unique dilemma. Perhaps most fundamentally, as strike action is designed to be disruptive it has the potential to impact the delivery of care and place patient well-being in jeopardy. The objective of this study is therefore to evaluate the impact of healthcare strike action on patient mortality outcomes globally using meta-analysis in order to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Our approach followed PRISMA guidelines 9 . Our study protocol was registered on PROSPERO (registration number CRD42021238879), peer reviewed, and published 10 …”
Section: Methodsmentioning
confidence: 99%
“…Our approach followed PRISMA guidelines 9 . Our study protocol was registered on PROSPERO (registration number CRD42021238879), peer reviewed, and published 10 …”
Section: Methodsmentioning
confidence: 99%
“…It is also noteworthy that in many cases, emergency services were able to be maintained or contingencies put in place to continue to deliver care with minimal disruption. On the second point, patient safety, it is difficult to comment on all elements of patient safety with the findings from this review alone, however and with the evidence noted in the introduction about patient morbidity 6 and mortality 7 during strike action, this body of evidence suggests that while disruptive, strikes can generally be conducted safely. There are of course several caveats, notably the more general limitations related to this evidence and the fact that strike action can come in a range of forms and have vastly different impacts on services.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies that have examined strike action have had similar difficulties, but also found that variables such as country, profession and other variables related to the nature of the strike had little impact of patient outcomes 59 . Throughout and perhaps because of this, we found a number of results that are perhaps unexpected, for example, while we might expect rural services to fare worst in low and middle income countries this was not always the case.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A strike is defined as a temporary stoppage of work by a group of employees to express a complaint or enforce a demand ( 1 ). Strikes can range from a simple interruption of the workday (for a few hours) or the reduction of non-critical services, to the complete stoppage of work as a last resort ( 2 ).…”
Section: Introductionmentioning
confidence: 99%